Iris stromal cell nuclei deform to more elongated shapes during pharmacologically-induced miosis and mydriasis. (January 2021) - Rashidi, Neda; Pant, Anup D.; Salinas, Samuel D.; Shah, Mickey; Thomas, Vineet S.; Zhang, Ge; Dorairaj, Syril; Amini, Rouzbeh
Abstract: Nuclear shape alteration in ocular tissues, which can be used as a metric for overall cell deformation, may also lead to changes in gene expression and protein synthesis that could affect the biomechanics of the tissue extracellular matrix. The biomechanics of iris tissue is of particular interest in the study of primary angle-closure glaucoma. As the first step towards understanding the mutual role of the biomechanics and deformation of the iris on the activity of its constituent stromal cells, we conducted an ex-vivo study in freshly excised porcine eyes. Iris deformation was achieved by activating the constituent smooth muscles of the iris. Pupillary responses were initiated by inducing miosis and mydriasis, and the irides were placed in a fixative, bisected, and sliced into thin sections in a nasal and temporal horizontal orientation. The tissue sections were stained with DAPI for nucleus, and z-stacks were acquired using confocal microscopy. Images were analyzed to determine the nuclear aspect ratio (NAR) using both three-dimensional (3D) reconstructions of the nuclear surfaces as well as projections of the same 3D reconstruction into flat two-dimensional (2D) shapes. We observed that regardless of the calculation method (i.e., one that employed 3D surface reconstructions versus one that employed 2D projected images) the NAR increased in both the miosis group and the mydriasis group. Three-dimensional quantifications showed that NAR increased from 2.52 ± 0.96 in control group to 2.80 ± 0.81 and 2.74 ± 0.94 in the mydriasis and miosis groups, respectively. Notwithstanding the relative convenience in calculating the NAR using the 2D projected images, the 3D reconstructions were found to generate more physiologically realistic values and, thus, can be used in the development of future computational models to study primary angle-closure glaucoma. Since the iris undergoes large deformations in response to ambient light, this study suggests that the iris stromal cells are subjected to a biomechanically active micro-environment during their in-vivo physiological function. Graphical abstract: Image 1 Highlights: The nuclear aspect ratio of porcine iris stromal cells was measured in vitro. Nuclei deform to more elongated shapes during miosis and mydriasis. Drug-induced deformation is more physiologically relevant than passive pulling. Changes were observed both in two- and three-dimensional measurements.